Pigment-protein complexes of thylakoid membranes of Deschampsia antarctica Desv. plants - Taran, N. Yu.; Ozheredova, I. P.; Storozhenko, V. O.; Svetlova, N. B.; Topchiy, N. M. (Ukrainian Antarctic Journal, 2010)
The molecular analysis results of pigment-protein complexes of photosynthetic membranes of Deschampsia antarctica plants, one of the native representatives of the Antarctic region are presented. Bioinformatics searching of genome products of Deschampsia antarctica in available protein databeses related to the structure and function of plastids was carried. The searching of Arabidopsis thaliana and Oryza sativa japonica homolog search submitted in free databases is also performed. The results of comparative analysis of primary sequences of the known and potential products are presented.